Peran Mahasiswa MBKM Bangun Desa dalam Kegiatan Psikoedukasi di Kelurahan Pengasinan - Fitri, Nadia Khalishah; Muzzamil, Ferdy (Yayasan Daarul Huda Kruengmane, 2024)
The program carried out this time aims to develop and implement psychoeducation that focuses on increasing the insight and knowledge of the community around Pengasinan Village regarding coping mechanisms and gadget addiction. The community service program that has been carried out in Pengasinan Village has the aim of developing knowledge on how to regulate emotions, how to respond to stressful conditions, how to control oneself when using gadgets, and avoiding the negative impacts of using these gadgets. The overall results of the MBKM Building Village program activities are helping parents deal with their children when they show different behavior than usual, building teenagers' awareness of the negative impacts they will receive if they are addicted to gadgets, and helping teenagers to create strategies for managing their time using their gadgets in everyday life.